If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 3x = x + 14 Combine like terms: 6x + 3x = 9x 9x = x + 14 Reorder the terms: 9x = 14 + x Solving 9x = 14 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 9x + -1x = 14 + x + -1x Combine like terms: 9x + -1x = 8x 8x = 14 + x + -1x Combine like terms: x + -1x = 0 8x = 14 + 0 8x = 14 Divide each side by '8'. x = 1.75 Simplifying x = 1.75
| m=3(1,6) | | 8x^2-59x+40=0 | | 14x^2+7x+14=0 | | 8(w-3)=16 | | |-3|-|2-17|= | | n+n+1+n+2+n+3=s | | 16-(5m+8)=5+2M-11 | | |11-2|-|3-1|= | | 6(w-2)=36 | | 70.56h=3.14 | | -12x-17=67 | | 1+5y=3 | | 120/10560= | | 4(2v+4)=170 | | 360=(4x-4)(3x+3) | | .75(7x+1)=-3 | | -4-43x=7x-6 | | 2(x-3)+5x=9x-14 | | 4(x-3)-3=-27 | | 10+5y=50 | | x^2+4q-45=0 | | t^2+3t-6=0 | | 3(-2x+1)-2(x+13)=7x-4(1-x) | | 2(3m-1)=16 | | 5(b+2)=30 | | 2x+6x=-8+7x | | 4y+3=21 | | 9(-4)-(-2)= | | 9x+9=7-(5x-6) | | -4(6x-7)+8(9x+7)=2 | | 11x^2-7x-10=0 | | -3(w-9)+8w+1= |